-5(n+3)-7+8n=

Simple and best practice solution for -5(n+3)-7+8n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(n+3)-7+8n= equation:


Simplifying
-5(n + 3) + -7 + 8n = 0

Reorder the terms:
-5(3 + n) + -7 + 8n = 0
(3 * -5 + n * -5) + -7 + 8n = 0
(-15 + -5n) + -7 + 8n = 0

Reorder the terms:
-15 + -7 + -5n + 8n = 0

Combine like terms: -15 + -7 = -22
-22 + -5n + 8n = 0

Combine like terms: -5n + 8n = 3n
-22 + 3n = 0

Solving
-22 + 3n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + 3n = 0 + 22

Combine like terms: -22 + 22 = 0
0 + 3n = 0 + 22
3n = 0 + 22

Combine like terms: 0 + 22 = 22
3n = 22

Divide each side by '3'.
n = 7.333333333

Simplifying
n = 7.333333333

See similar equations:

| j/3=2/5 | | -5(z+3)+4(3z-4)=6(z-3)+14 | | 6(3-2x)=1-(2x-1) | | 4-7+8=4(n)+4(n) | | -2x+9=-3x+29 | | 7x-16=6x-12 | | Z=5+2i | | -4(x-2)=4(2x+5) | | -log*(x)=0.85 | | 20x+25=19x+29 | | a(1+2a)-a(4a-5)= | | 25x^4=61x^2-36 | | 12(h-1)=6h+4+2 | | -2m+0=180(-49y) | | 198=x+2*x*2 | | 14+5(2x+2)=-5 | | 8+3x+4=10 | | 198=x+2+x+2 | | 7-2n-n=-14 | | 12/42=4w/56 | | -2+0=180(-49y) | | w=3ab | | x/8.9=22 | | 2z+8=4z-4 | | 4(2x-5)=-2(7-3x) | | -150h=400 | | 4x-1=2x-1+x+2 | | 198=l*w*h | | 4x-50=3x+50 | | 0=-16t^2+30t+5 | | 5x-22+8x+46=180 | | t+9-8=5 |

Equations solver categories